La interpretación antigua de los versos líricos de Horacio - Castillo Herrera, Marina del (1991)
The relatively reduced number of ancient works related to the metrics of horace´s odes and epodes, as well as the limitted number of metric forms appearing in these poetic works, make posiible an extended study of all of them in ancient metrics. this type of study allows, on the one hand, a clear understanding of the devices in ancient metrics; these become clear once they are applied on metrical structures other than the datylic-iambic ones. On the one hand, this type of study may shed some light on Horace´s understanding of metrics. This paper presents a detailed description of the interpretation of horace´s lyric metres in ancient artes grammaticae and metricae, and scholia.
Keywords: Horacio Flaco, Quinto; Poesía lírica